2015
DOI: 10.1099/jmm.0.000159
|View full text |Cite
|
Sign up to set email alerts
|

Trichosporon inkin biofilms produce extracellular proteases and exhibit resistance to antifungals

Abstract: The aim of this study was to determine experimental conditions for in vitro biofilm formation of clinical isolates of Trichosporon inkin, an important opportunistic pathogen in immunocompromised patients. Biofilms were formed in microtitre plates in three different media (RPMI, Sabouraud and CLED), with inocula of 10 4 , 10 5 or 10 6 cells ml 21, at pH 5.5 and 7.0, and at 35 and 28 8C, under static and shaking conditions for 72 h. Growth kinetics of biofilms were evaluated at 6, 24, 48 and 72 h. Biofilm milieu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 50 publications
1
20
0
1
Order By: Relevance
“…Concentration of rhamnolipid and amphotericin B corresponding to the lowest FIC had an effect equal to that of the individual substances applied in their MIC. Cordeiro et al (2015) and Liao et al (2015) reported similar results; an almost complete suppression of biofilm formation needed a much higher concentration of amphotericin B than inhibition of planktonic cells.…”
Section: Effect Of Rhamnolipid and Amphotericin B On Biofilm Formationsupporting
confidence: 76%
See 1 more Smart Citation
“…Concentration of rhamnolipid and amphotericin B corresponding to the lowest FIC had an effect equal to that of the individual substances applied in their MIC. Cordeiro et al (2015) and Liao et al (2015) reported similar results; an almost complete suppression of biofilm formation needed a much higher concentration of amphotericin B than inhibition of planktonic cells.…”
Section: Effect Of Rhamnolipid and Amphotericin B On Biofilm Formationsupporting
confidence: 76%
“…Adhesion of microbial cells is linked with cell phenotype variations, which are usually manifested by new metabolic pathways, enhanced virulence and, as in the basis of this work, increased resistance to antimicrobial compounds (Nikolaev and Plakunov 2007). Biofilm resistance to various types of antimicrobial agents including biocides, antibiotics, and antiseptics is well reported (Cordeiro et al 2015;Donlan and Costerton 2002;Gilbert et al 2002;Leung et al 2012;Liao et al 2015). Although this phenomenon was firstly described for bacterial biofilms, yeast infections caused by biofilms, including Candida and Trichosporon, were also reported to exhibit high drug resistance (Al-Fattani and Douglas 2006;d'Enfert 2006;Di Bonaventura et al 2006).…”
Section: Introductionmentioning
confidence: 98%
“…C. albicans biofilms were fixed with 2.5 % glutaraldehyde in 0.15 M of sodium cacodylate buffer with Alcian blue (0.1 %), incubated overnight at 4 °C, dehydrated with an ascending ethanol series, dried with hexamethyldisilazane (Polysciences Europe, Hirschberg an der Bergstraße, Germany), coated with 10 nm of gold (Emitech Q150T, Quorum Technologies Ltd, Laughton, UK) and observed with an FEI Inspect S50 scanning electron microscope (Brno, Czech Republic) operating in high-vacuum mode at 15 kV [17].…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…fibuligera is a nonpathogenic yeast which has been employed as a comparator in C. tropicalis gut inflammation studies (17, 18). Next, we determined the ability of the designed probiotic to prevent and treat PMB formed by C.…”
Section: Introductionmentioning
confidence: 99%